Development of integrated reverse logistics networks for electronic waste and lithium-ion battery recycling – a case analysis of South Africa - Vooght, Dominic Terence (Stellenbosch : Stellenbosch University, 2025)
Vooght, D. T. 2025. Development of integrated reverse logistics networks for electronic waste and lithium-ion battery recycling – a case analysis of South Africa. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/e11419cb-20eb-4a46-918b-0b436d7408e7